1986
DOI: 10.1530/jrf.0.0760115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyamine limitation on DNA synthesis and development of mouse preimplantation embryos in vitro

Abstract: Summary. In-vitro treatment of preimplantation mouse embryos with spermine and spermidine biosynthesis inhibitor, methylglyoxal-bis-(guanylhydrazone) (MGBG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In vertebrates, there is little evidence for a developmental role for ODC other than inhibitor studies. For example, in vitro depletion of spermine and spermidine by an inhibitor of S-adenosyl-L-methionine decarboxylase arrests growth before the eight-cell or morula stage of fertilized murine embryos, whereas DFMO, a potent inhibitor of ODC, arrests development at the morula-to-blastocyst transition (54). Furthermore, chicken embryos injected with DFMO have marked reductions in their polyamine levels and fail to develop past gastrulation (22).…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, there is little evidence for a developmental role for ODC other than inhibitor studies. For example, in vitro depletion of spermine and spermidine by an inhibitor of S-adenosyl-L-methionine decarboxylase arrests growth before the eight-cell or morula stage of fertilized murine embryos, whereas DFMO, a potent inhibitor of ODC, arrests development at the morula-to-blastocyst transition (54). Furthermore, chicken embryos injected with DFMO have marked reductions in their polyamine levels and fail to develop past gastrulation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Implantation sites in the mouse display elevated levels of expression of Odc1 and polyamines (Zhao et al, 2008). Blockade of Odc1 conversion of ornithine to the polyamine putrescine by the suicide inhibitor difluoromethyl ornithine (DFMO) prevents implantation in the mouse (Zhao et al, 2008) and reversibly arrests development in mink (Lefevre et al, 2011b) and mouse (Zwierzchowski et al, 1986) embryos. Expression of ODC1, along with the polyamine availability genes (Lefevre et al, 2011a) and uterine content of the polyamine putrescine (Lefevre et al, 2011b), are upregulated at the termination of diapause in the mink (Murphy, 2012).…”
Section: The Uterus Dictates Diapausementioning
confidence: 99%
“…Studies employing inhibitors of polyamine biosynthesis have indicated that an inhibition of ODC will arrest murine embryonic development at the morula‐blastocyst stage and an inhibition of AdoMetDC at an even earlier stage [136]. Moreover, DFMO induces resorption of murine embryos when given just after the first week of gestation [137,138].…”
Section: Odcmentioning
confidence: 99%
“…AdoMetDC‐deficient embryos developed normally to the blastocyst stage, but died shortly thereafter or during the early stage of gastrulation at the latest. They developed distinctly further than did embryos cultured in the presence of an inhibitor of AdoMetDC, methylglyoxal bis(guanylhydrazone) [136]. When cultured in vitro , AdoMetDC‐deficient blastocysts showed an absolute growth requirement for spermidine [142].…”
Section: Adometdcmentioning
confidence: 99%
See 1 more Smart Citation